2000
DOI: 10.1071/ar99132
|View full text |Cite
|
Sign up to set email alerts
|

Blood prolactin depression in growing pigs fed sorghum ergot (Claviceps africana)

Abstract: The toxicity of sorghum ergot (Claviceps africana) was assessed in young pigs over 28 days. Forty-eight pigs of both sexes and 2 breeds (Large White and Duroc) were allocated across 6 grower diets, balanced for fibre and predicted digestible energy, and containing 0, 0.3, 0.6, 1.3, 2.5, or 5% ergot sclerotia [the 5% sclerotia diet contained 70 mg alkaloids/kg (>90% dihydroergosine)]. Blood samples taken on Days 0 and 28 were analysed for prolactin and clinical, biochemical, and haematological indices of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The cause is not a systemic effect, as shown by our observation that consumption improved when the flavour was disguised, and is probably caused by factors in ergot other than alkaloids. Addition of palatable ingredients, such as full‐fat soy meal, during formulation has previously shown to overcome the feed refusal problem (Blaney et al., 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…The cause is not a systemic effect, as shown by our observation that consumption improved when the flavour was disguised, and is probably caused by factors in ergot other than alkaloids. Addition of palatable ingredients, such as full‐fat soy meal, during formulation has previously shown to overcome the feed refusal problem (Blaney et al., 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Although observed no nutritional changes in maize as a result of F. graminearum infection, some previous studies have shown that weather damage (Taverner et al, 1975;Batterham et al, 1976) and fungal infection of grains (Kopinski and Blaney, 1999;Blaney et al, 2000) can lower their digestible energy. Consequently in this study, an additional treatment group was offered a diet (B + E) supplemented with 1 MJ/kg of energy (3% additional oil) to compensate for the anticipated lower DE value of white grain wheat.…”
Section: Digestibility Of Nutrientsmentioning
confidence: 92%
“…Sorghum ergot was first detected in Australia in 1996 7 and has subsequently been found in all sorghum‐producing regions 8 . Our initial investigations into its potential toxicity showed that plasma prolactin concentrations were reduced in grower pigs by sorghum ergot 9,10 . In mid 1997, reports were received from 10 piggeries located about 150 km south‐west of Rockhampton in Queensland, of severe feed refusal and death of piglets, as sows failed to lactate after farrowing 11 .…”
mentioning
confidence: 99%
“…8 Our initial investigations into its potential toxicity showed that plasma prolactin concentrations were reduced in grower pigs by sorghum ergot. 9,10 In mid 1997, reports were received from 10 piggeries located about 150 km south-west of Rockhampton in Queensland, of severe feed refusal and death of piglets, as sows failed to lactate after farrowing. 11 Sorghum grain from these piggeries contained 1 to 20% by weight of ergot sclerotia and the resultant pig diets contained 20 to 40 mg alkaloids/kg, predominantly DHES.…”
mentioning
confidence: 99%